Communicating your research with social media a practical guide to using blogs, podcasts, data visualisations and video - Mollett, Amy; Brumley, Cheryl; Gilson, Chris; Wiliams, Sierra (London SAGE Publications Ltd, 2017)
This dynamic, engaging guide empowers you to go beyond bar charts and jargon-filled journal articles to bring your research online and present it in a way that highlights and maximises its relevance through social media. Drawing upon a wealth of timely, real-world examples, the authors present a framework for fully incorporating social media within each step of the research process. From visualising available data to tailoring social media to meet your needs, this book explores proactive ways to share cutting edge research.
Includes bibliographical references and index.
Keywords: Social media; Blogs; Podcasts; Research -- Technological innovations